Buckling of externally pressurised spherical caps with wall-thickness reduction. (March 2019) - Zhang, Jian; Wang, Yueyang; Tang, Wenxian; Zhu, Yongmei; Zhao, Xilu
Abstract: This study examined the buckling of spherical caps fabricated under different conditions of wall-thickness reduction. The spherical caps were fabricated using photosensitive resin and had a base diameter of 150 mm and height of 41.1 mm; they were subjected to uniform external pressure. In total, 42 spherical caps—6 with full thickness reduction and 36 with partial thickness reduction—were fabricated through rapid prototyping; after their external surface and wall thickness were measured, all caps were tested to collapse to experimentally and numerically evaluate their buckling properties, namely buckling pressures and collapse modes. Moreover, the effects of site, magnitude, and range of the thickness reduction on the buckling properties were evaluated. Herein, the experimental and numerical results are comparatively presented in tables and figures. Highlights: Spherical caps of various site, range, and magnitude of thickness reduction were built. Buckling pressures and collapse modes of 42 such caps were obtained experimentally. A semianalytical formula for evaluating their load-bearing capacity is identified.